Behind the scenes: the roles of reactive oxygen species in guard cells. Issue 4 (5th November 2013) - Song, Yuwei; Miao, Yuchen; Song, Chun‐Peng
Summary: Guard cells regulate stomatal pore size through integration of both endogenous and environmental signals; they are widely recognized as providing a key switching mechanism that maximizes both the efficient use of water and rates of CO2 exchange for photosynthesis; this is essential for the adaptation of plants to water stress. Reactive oxygen species (ROS) are widely considered to be an important player in guard cell signalling. In this review, we focus on recent progress concerning the role of ROS as signal molecules in controlling stomatal movement, the interaction between ROS and intrinsic and environmental response pathways, the specificity of ROS signalling, and how ROS signals are sensed and relayed. However, the picture of ROS‐mediated signalling is still fragmented and the issues of ROS sensing and the specificity of ROS signalling remain unclear. Here, we review some recent advances in our understanding of ROS signalling in guard cells, with an emphasis on the main players known to interact with abscisic acid signalling.   Contents     Summary 1121 I. Introduction 1121 II. Multiple signals for production and signalling integration of ROS in guard cells 1122 III. Signal transduction pathway of ROS in guard cells 1125 IV. Specificity of ROS signalling 1129 V. Conclusions and prospects 1133   Acknowledgements 1134   References 1134